1990
DOI: 10.1099/00221287-136-8-1551
|View full text |Cite
|
Sign up to set email alerts
|

Artificial insertion of peptides between signal peptide and mature protein: effect on secretion and processing of hybrid thermostable  -amylases in Bacillus subtilis and Escherichia coli cells

Abstract: To study the effect of inserted peptides on the secretion and processing of exported proteins in Bacillus subtifis and Escherichia cofi, pBR322-derived DNA fragments coding for small peptides were inserted between the DNA coding for the 31 amino acid B. subtifis a-amylase signal peptide and that coding for the mature part of the extracellular thermostable a-amylase of B. stearothermophifus. Most of the inserted peptides (21 to 65 amino acids) decreased the production of the enzyme in B. subtifis and E. cofi, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This improvement was accompanied by a two-to fourfold increase in the amounts of Nuc-secreted product (up to 20 mg per liter). Similar experiments in which several synthetic peptides were inserted just after the signal peptide in a heterologous hybrid protein in B. subtilis resulted in slightly enhanced secretion; however, processing occurred at an altered cleavage site (14). In contrast to the results of those previous studies, LEISSTCDA-Nuc fusions conserve the original cleavage site.…”
Section: Discussionmentioning
confidence: 47%
“…This improvement was accompanied by a two-to fourfold increase in the amounts of Nuc-secreted product (up to 20 mg per liter). Similar experiments in which several synthetic peptides were inserted just after the signal peptide in a heterologous hybrid protein in B. subtilis resulted in slightly enhanced secretion; however, processing occurred at an altered cleavage site (14). In contrast to the results of those previous studies, LEISSTCDA-Nuc fusions conserve the original cleavage site.…”
Section: Discussionmentioning
confidence: 47%
“…Instead, we believe that they are removed by the several nonspecific proteases secreted by Bacillus species. This mechanism is supported by the facts that artificial propeptides can also be accurately removed (139), as can natural propeptides when fused to such proteins that do not normally contain them (319). Furthermore, when B. licheniformis 3-lactamase was produced in a B. subtilis mutant with low exoprotease activity, a much greater percentage of the enzyme remained cell associated at late growth phases than that in wild-type B. subtilis (245).…”
Section: Propeptidesmentioning
confidence: 99%
“…The different lengths of signal peptides may be related to differences in the structure of signal peptidases or other secretion components in gram-positive and gram-negative bacteria. For example, the signal peptidases of E. coli and Bacillus species often cleave the same signal peptides at different sites, E. coli favoring cleavage sites that produce shorter signal peptides than those of Bacillus species (139,284,332,342).…”
Section: Signal Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal peptide cleavage sites were determined by the NH2-terminal amino acid sequences of the exported thermostable a-amylases from the hybrid genes. It has been shown that a possible secondary proteolysis in the a-amylase preparations did not occur or was negligible under the present culture conditions with the protease-deficient B. subtilis strain and E. coli HB101 as the host cells and during the subsequent purification steps under hydrophobic conditions (11,12 subtilis. (b) Nucleotide and predicted amino acid sequences around the junction regions of B. subtilis ax-amylase signal peptide (amyE') and the mature thermostable a-amylase ('amyT) of B. stearothermophilus A631 in plasmids pTUBE691, pTUBE693, and pTUBE695, in which one, two, and three Ala-X-Ala sequences were inserted, respectively.…”
mentioning
confidence: 92%